Possible futures for Geography and Geographers and Political Geography? A reading from the margins - McConnell, F (Springer, 2020)
In thinking about the present utility and possible futures for Geography and Geographers and Political Geography this contribution focuses on the perspective of the margins. At first glance, both books are written from the perspective of the core, yet, margins, in various guises, are frequently mentioned in both texts and in many ways underpin the political agenda behind these volumes. That said, both present rather static views of the margins and, in terms of possible futures for these books, this contribution discusses how they might bring the margins centre-stage in more dynamic ways. For Political Geography, it is suggested that the creative tension between post-colonial studies and the world-systems approach might usefully be brought to the fore in the book and the volume reworked so that it is written from the vantage point of the margins. In terms of Geography and Geographers the suggestion is to augment the format in order to make the book a less ‘comfortable’ read. Akin to the ‘choose your own adventure’ books that were popular when both volumes were first published, an interactive digital platform accompanying the book might provide a vantage point from which the medley of margins that is contemporary human geography might more clearly come into view.